Konsep Akad Qard Alhasan dalam Pengembangan Pembiayaan Pedidikan di Bank Mini Syariah UIN Sunan Ampel Surabaya - Najlatus Syarifah Roihana; Siti Alfia Nur Rohmayanti (Jaanur Elbarik Indonesia, 2025)
The Qard-Al Hasan contract is a form of sharia-compliant financing that focuses on social aspects and benefits. In the development of educational funding at Bank Mini Syariah UIN Sunan Ampel Surabaya, this contract plays a crucial role as an alternative option that complies with sharia principles to meet the educational funding needs of underprivileged communities. This article aims to explain the meaning and application of the Qard-Al Hasan contract in the context of developing educationalfinancing. Through a literature review and conceptual analysis, it was found that this contract not only provides financial benefits such as cost efficiency but also increases public trust and loyalty to Islamic financial institutions. The main challenges faced include credit risk and a lack of public information about the benefits and how this contract works. With strategic implementation and appropriate education, the Qard-Al Hasan contract can be an effective tool in supporting the sustainability of sharia-compliant educational financing and strengthening the role of Islamic financial institutions in society.